The Seal of Confession under the Legislation of Ukraine - Oleksandr Bilash; Tetyana Karabin; Pavlo Cherevko (Kościół i Prawo)
The article is devoted to the study of the seal of confession legal protection by Ukrainian legislation under the circumstances of its formation and development. The conducted analysis has given grounds to make up conclusions concerning the “three levels” of regulation and protection of the seal of confession by the legislation of Ukraine, depending on the conditions and circumstances of the confession. The general legal protection of the seal of confession is accomplished through the provisions of the Law “On Freedom of Conscience and Religious Organizations” as well as procedural codes regarding the prohibition of demanding the information obtained from believers by clergymen during the confession and interrogating them as witnesses. Information entrusted to a military chaplain by a serviceman has a higher degree of legal protection, as such an information acquires the status of confidential. The highest degree of legal protection under Ukrainian legislation is established for confessions made in penitentiary institutions. For such confessions, prohibitions on the disclosure of information apply not only to priests, but also to other persons: employees of penitentiary authorities, the court, an interpreter. There are also positive obligations to create conditions for confession and ensure its secrecy.